(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The study is aimed at studying technological trends in the digital transformation of corporations, large and medium-sized enterprises. Changes in business management are considered, taking into account global technological trends, and an analysis of the results of activities in this area is carried out. The basic concepts of "digital transformation" are given from the point of view of international organizations. The growth rate of digital transformation before and after the COVID-19 pandemic is analyzed.